Judge Clyde Cahill: Courage and Action - Hon. David Mason (Washington University Journal of Law and Policy, 2022)
In a democratic society, it is essential that a competent and independent judiciary act as a bulwark against any force that seeks to strip citizens of their fundamental rights. The essence of this judiciary is judges with an open and notorious commitment to both uphold and enhance the law. The Honorable Clyde S. Cahill was one such judge. This Article discusses the life and work of Judge Cahill and highlights how the Judge was a trailblazer that set a clear path to improving judicial outcomes. Judge Mason traces Cahill’s life story from his early beginnings, growing up in a poor family, to his rise as a judge determined to bring fairness and equity to the judicial administration of criminal law and civil rights. Judge Mason focuses on specific findings and opinions of Judge Cahill which aimed to improve equal rights and due process at the trial level in our state and federal courts, including Judge Cahill’s longstanding criticism of the racial implications of mandatory sentencing. The author illustrates Judge Cahill’s persistence, suggesting that his visionary work serves as a model for what the judiciary in a democracy should be.
Keywords: Honorable Clyde S. Cahill; Judiciary; Mandatory Sentencing